CORN SEED DRYER UTILISING HEATING ELEMENT AND COLOUR DETECTION WITH ESP32-CAM - Rifandi, Ahmad; Sulistiyowati, Indah; Ahfas, Akhmad; Jamaaluddin, Jamaaluddin (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
This study designed a corn grain dryer based on the ESP32-CAM microcontroller to enhance the efficiency of the post-harvest drying process. An expedited alternative to conventional drying that remains contingent upon weather conditions. The efficacy of the engineered apparatus was assessed via an experimental methodology. The apparatus for assessing the color of corn kernels comprises an ESP32-CAM camera, a heating element, and a K-type thermocouple sensor. The ESP32 microprocessor operates the system of this device. Experiments were performed by contrasting the drying outcomes with traditional methods. The gadget can desiccate corn kernels in 30 minutes to 2 hours for 0.5 kg, which is considerably more efficient than conventional methods. The automated mechanism maintains the optimal drying temperature range between 38 and 40°C. The method is deemed complete when the camera accurately identifies the color transition of the maize kernels from moist (yellow) to dry (golden). Due to its versatility for use at any moment.